2023
DOI: 10.1530/erc-22-0287
|View full text |Cite
|
Sign up to set email alerts
|

Diagnosis and management of parathyroid carcinoma: a state-of-the-art review

Abstract: Parathyroid carcinoma is one of the least common endocrine malignancies, and accounts for approximately 1% of all patients with primary hyperparathyroidism. A systematic review of peer-reviewed literature published between January 2000 and March 2022 via Medline, Embase, Cochrane Central Register of Controlled Trials, EudraCT, ClinicalTrials.gov, CINAHL and SCOPUS was conducted. Manuscripts were eligible if they included data on adult non-pregnant populations with parathyroid carcinoma. No restrictions regardi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
38
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 15 publications
(76 citation statements)
references
References 74 publications
(134 reference statements)
0
38
0
Order By: Relevance
“…PTH, neuroendocrine tumor markers SYN, and CgA are helpful in the diagnosis of PC; when the Ki-67 index is greater than 5%, it is alert to consider the possibility of malignancy. 3 In this case, the tumor tissue was heavily fibroussegregated and the tumor cells were heterogeneous with obvious Radical resection of the tumor lesions at the first surgery is the only chance to cure PC potentially. 3 Up to now, there is no evidence to show survival benefits from chemotherapy, radiotherapy and immunotherapy in the treatment of PC.…”
Section: Discussionmentioning
confidence: 79%
See 4 more Smart Citations
“…PTH, neuroendocrine tumor markers SYN, and CgA are helpful in the diagnosis of PC; when the Ki-67 index is greater than 5%, it is alert to consider the possibility of malignancy. 3 In this case, the tumor tissue was heavily fibroussegregated and the tumor cells were heterogeneous with obvious Radical resection of the tumor lesions at the first surgery is the only chance to cure PC potentially. 3 Up to now, there is no evidence to show survival benefits from chemotherapy, radiotherapy and immunotherapy in the treatment of PC.…”
Section: Discussionmentioning
confidence: 79%
“…7 Mutations of the cell division cycle 73 (CDC73) gene has been reported as the most common tumor suppressor gene associated with PC and the absence of parafibromin caused by mutations of CDC73 makes parathyroid tissue more susceptible to carcinogenesis. 3,6 In addition, studies have also suggested that repeated mutations of the Prune Homolog 2 with BCH Domain (PRUNE2) gene and AarF Domain-Containing Kinase 1 (ADCK1) gene, genetic amplification of Cyclin D1 gene, and abnormal activation of PI3K/AKT/mTOR signaling pathway are related to the occurrence of PC. 6,8 In this case, there were not any abnormalities found in the above common genes' detection, and the specific etiology of this patient still needs to further study.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations